The complete chloroplast genome of Blepharis ciliaris (Acanthaceae) - Yaradua, Samaila S. (Mitochondrial DNA B Resour, 2019)
Blepharis ciliaris is an important medicinal plant and endemic species in Saudi Arabia. This study reported the complete chloroplast genome of B. ciliaris, the second to be sequence in non cystolith clade of Acanthaceae. The genome is 149, 717 bp in size and consisted of a pair of inverted repeat (25, 331 bp each) separating the two single copy region, the large single copy (LSC) 82, 057 bp and small single copy SSC 16, 998 bp. The plastome has overall GC content of 38.5% and 112 genes comprising of 79 protein coding genes, 30 tRNA genes and 4 rRNA genes. The phylogenetic relationship analysis showed that B. ciliaris is sister to Aphelandra knappiea. The cp genome reported in this study will useful in genetic diversity and evolutionary studies of the species.